Development of a Solar Dryer with Multi-Products and a Residual Moisture Control System - Nafisa A. ABDULHAMID; Danladi D. USMAN; Kabiru I. JAHUN; Rotkangmwa J. SATI; Yahaya U. JAURO; Abdulmajid M. HASHIR; Yusuf G. SHIMBURA (FUDMA Journal of Engineering and Technology, 2026)
By using solar energy to heat air and dry food materials, a solar drying system helps preserve and reduce agricultural produce waste. It also makes it easier to transport dried produce, which improves people's health and well-being. The project's goal is to create a solar dryer with a residual moisture control system that may shorten drying times and yield high-quality goods. Mild steel, collector glass, angle iron, metal sheet, aluminum foil, plywood, steel mesh wire, 12 V fans, and other materials were purchased locally for the production. A solar drying chamber with a rack of four wire mesh (net) trays and a solar collector (air heater) make up the dryer. The solar collector heats the air that enters through the air inlet before directing it into the drying chamber, where it is used for drying (removing the moisture content from the food ingredient or agricultural produce loaded). Temperature and humidity sensors, a control switch, and a 12V fan make up the residual moisture control system. It is anticipated that the dryer, which has a collector area of 0.637 m2, a drying chamber measuring 700 × 1325 × 600 mm, a collector inclination (β) of 20.17 o, insulation thickness (tb) of 1.5 mm, and insolation on the collector (Ic) of 1215.15 W/m2, will dry two to three kilograms of goods. By enlarging the solar collector, current solar food driers can still be made better, particularly in terms of eliminating any remaining moisture and likely storing heat inside the system.
Keywords: Solar dryer, Solar collector, Residual moisture, Insulation, Polyurethane glass.